2021
DOI: 10.1186/s12905-021-01287-4
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of local recurrence following implant-based breast reconstruction in breast cancer patients

Abstract: Background The number of patients desiring implant-based breast reconstruction has been increasing. While local recurrence is observed in patients with breast reconstruction, only a few reports have focused on the risk factors for local recurrence and the prognosis after developing local recurrence. Methods We analyzed 387 patients who underwent implant-based breast reconstruction during the period from 2004 to 2017 in Hiroshima City Hospital. We r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…In immediate implant-based ( 19 ) and autologous ( 20 ) breast reconstruction studies, LVI, tumor staging, multifocality, and absence of hormonal therapy were risk factors associated with local regional recurrence. The novel nomogram further confirmed that younger age, comorbidities, advanced tumor staging, bilateral malignancy, and higher number of positive lymph nodes were associated with worse DFS.…”
Section: Discussionmentioning
confidence: 99%
“…In immediate implant-based ( 19 ) and autologous ( 20 ) breast reconstruction studies, LVI, tumor staging, multifocality, and absence of hormonal therapy were risk factors associated with local regional recurrence. The novel nomogram further confirmed that younger age, comorbidities, advanced tumor staging, bilateral malignancy, and higher number of positive lymph nodes were associated with worse DFS.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated the potential benefits of implant-based breast reconstruction and oncological outcomes. Fujihara et al 41 showed that the local recurrence rate after implant-based breast reconstruction was 3.1%. In our analysis, the recurrence rates for breasts undergoing prepectoral IBBR were 2.77% (14/504) and subpectoral IBBR was 1.91% (7/366).…”
Section: Discussionmentioning
confidence: 99%
“…Patient related factors include elevated body mass index, advanced age, and young age. 15,16 Rough textured implants have raised concerns about both implant related anaplastic large cell lymphoma's as well as local primary recurrence. 17 Leaving the skin immediately overlying the initial tumor and the needle track site of a core needle biopsy have been implicated in LR.…”
Section: Introductionmentioning
confidence: 99%
“…17 Leaving the skin immediately overlying the initial tumor and the needle track site of a core needle biopsy have been implicated in LR. 18 Furthermore, radiation increases risk of complications, including infection, skin necrosis, and loss of reconstruction for both autologous and prosthetic. 5 Therefore, those receiving radiation, may see stronger bene ts when delayed reconstruction is performed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation